2022
DOI: 10.1101/2022.12.06.519344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Mapping of Progressive Ethanol Consumption in the Diversity Outbred Mouse

Abstract: Traditional genetic mapping studies using inbred crosses are a powerful tool for identifying chromosomal regions associated with ethanol-related traits, but typically have very large confidence intervals which make identification of specific and potentially causal candidate genes difficult. Diversity Outbred (DO) mice offer the ability to map quantitative trait loci (QTLs) associated with ethanol-drinking behaviors at a high resolution that allows for easier identification of candidate genes. Here, we exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 96 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…From our analyses, certain myelin structural genes such as Mbp, Mobp, and Mag were significantly positively correlated with ethanol consumption. Of these, Mbp was a key driver of the orange module, and one of its interacting proteins ( Ticam1 ) showed significant correlation to ethanol consumption or preference [18]. This an interesting finding, as previous studies have shown a reduction in myelin gene expression with ethanol exposure.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…From our analyses, certain myelin structural genes such as Mbp, Mobp, and Mag were significantly positively correlated with ethanol consumption. Of these, Mbp was a key driver of the orange module, and one of its interacting proteins ( Ticam1 ) showed significant correlation to ethanol consumption or preference [18]. This an interesting finding, as previous studies have shown a reduction in myelin gene expression with ethanol exposure.…”
Section: Discussionmentioning
confidence: 92%
“…636 DO mice were used for intermittent access ethanol drinking by 3-bottle choice for 11 drinking days over 4 weeks (Figure 1a). As discussed in a previous publication, these mice significantly increased the total amount of ethanol they consumed over the course of the study [18]. Of these, 200 mice were selected for RNAseq analysis, as RNAseq on 636 mice would have been cost prohibitive.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations